Morfometria de Psectrogaster amazonica (Characiforme: Curimatidae), Triportheus sp. (Triportheus) e Pellona castelnaeana (Clupeiformes: Pristigasteridae) da ictiofauna do médio Rio Tocantins em Imperatriz, Maranhão, Brasil - Barbosa, Letícia Almeida (2023)
The Neotropical freshwater ichthyofauna is the richest in species in the world, and is considered the largest group of vertebrates in existence and with greater adptive success to aquatic ecosystems. Moreover, the Tocantins River is inserted in the Araguaia-Tocantins basin, considered still important for the Neotropical biodiversity with an abundant biodiversity. In this sense, also considering that morphometry contributes to the study of the shapes and sizes of individuals of the same species and between distinct species, besides numerical estimates being used by statistical methods, the study aims to characterize three fish species from the middle Tocantins River through statistical analysis. For the construction of the database three fish species were captured: Triportheus sp., Psectrogaster amazonica, Pellona castelnaeana using trawls and fishing nets with mesh sizes varying from 5mm, 7mm and 36mm. The fish were collected from sections of the Tocantins River such as Cacauzinho, Beira Rio, and Embiral. Soon after, the specimens were identified, following specific literature, and stored in freezer (-20 °C) in the Laboratory of Genetics and Molecular Biology – LabGeM of the Universidade Estadual da Região Tocantina do Maranhão – UEMASUL. Microsoft Excel 2016 and R version 4.2.2 software was used for the statistical analyses, evaluating 7 variables of the three species under study: Standard Length (PC), Total Length (CT), Head (CC), Snout Length (FC), Eye Diameter (OD) and Height (AT) and Weight (W) and classified according to the degree of correlation. A total of 32 individuals of the species Triportheus sp., 42 of the species Psectrogaster amazonica and 43 of the species Pellona castelnaeana were collected and the analyses of comparison were made by means of Person’s correlation analysis and Linear regression analysis. In the mean analysis it was observed that the highest means were for the species Pellona castelnaeana and the closest standard deviation in the species Psectrogaster amazonica and Triportheus sp. Regarding the Person analysis, in the Psectrogaster amazonica species, CF was the only variable that did not show significant correlations Triportheus sp. showed significant correlations between the variables CP and P, but weak. Something that was not observed in Curimata amazônica specimens, since they did not show correlations with any of the variables analyzed. Future studies on the sex and age of the fish are needed to analyze how regional anthropic problems have interfered in the morphometric characteristics of these species, also taking into consideration the factors that contribute to the decrease in the quality of the fish